The political constitutions of Peru before international law - Malapi Hernández, Daniela Francesca (2022)
After celebrating the Bicentennial of the independence of Peru, this article aims to relate the main events that have occurred in the future of international law, as well as its advances in the normative plane, and the most important provisions that were enshrined in the political constitutions given in our historical development. This relationship made possible the implementation of the international legal order in domestic law. In the first part, there will be a review of the main milestones in the history of international law that gave the guidelines for the original structure of the first Peruvian Constitution, in the second and third part, the main constitutional provisions that welcomed different categories and principles will be identified of international law in force since and during the 19th century and the 20th century, respectively, and which in turn contributed to the consolidation of certain concepts and legal norms that are present today in various international instruments.